The Silent Architecture of Science Learning: A Critical Analysis of Visual Representations in Indonesian Integrated STEM Textbooks - Bevo Wahono; Astrino Purmanna; Jose Arturo Molina Bravo (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
This study aimed to analyze visual content on Indonesian junior high school science textbooks by discovering characteristics and patterns of STEM-related content. Textbooks could be a great vehicle to promote the interlinked importance of science, technology, engineering, and mathematics disciplines in a compact context. Therefore, analyzing the visual patterns and characteristics in the science textbook is paramount. The samples in this current study consisted of science textbooks from grade IX, specifically two of the most widely used science textbooks in Indonesia. The type, function, and pattern of the STEM-related contents were the main focuses. The results showed significant differences in the type, function, and pattern of STEM-related content in the selected textbook. Moreover, this current study reveals a poor, unequal representation of the type, function, and pattern of STEM-related content in the textbook. This empirical evidence, in the form of visualizing patterns and characteristics, is crucial, primarily to guide science teachers to utilize science textbooks in their everyday school life. Other essential implications are also discussed in this study, primarily pertaining to publishers, academia, and educational policymakers in Indonesia and other countries worldwide.